Meaning of Ambiguity: A Japanese Survey on Synthetic Biology and Genome Editing - Hibino, Aiko; Yoshizawa, Go; Minari, Jusaku (Frontiers in Sociology, 2019)
Synthetic biology and genome editing have become increasingly controversial issues, necessitating careful attention and engagement with the public. Our study examined ambiguity in public perception about emerging biotechnologies through the use of several intermediate response options in a survey. To understand the relationship between respondents’ thoughts and attitudes, we also examined how respondents’ indecision is related to their cognitive concept of “self” as well as their interpretation of “future generations.” An online survey of 994 respondents living in Japan revealed that around 80% hold intermediate attitudes (two-sided, non-judgmental, or reserved attitudes) toward synthetic biology and genome editing. These results revealed that respondents who have a narrow self-concept tend to postpone decisions about the application of emerging technologies. In contrast, those with a broad self-concept tend to adopt an ambivalent attitude and are more short-sighted, but make judgments based on the impact of their decisions on current and future generations. This study thus demonstrates that public views are more diverse and nuanced than those obtained from conventional public surveys for policy making.